REACTIVE POWER CONTROL OF WIND FARM USING FACTS DEVICES - Ashfaq, Sara; Arif, A.; Shakeel, A.; Mahmood, T. (The Nucleus, 2014)
Wind energy is an attainable option to complement other types of pollution-free green generation Grid connections of renewable energy resources are vital if they are to be effectively exploited, but grid connection brings problems of voltage fluctuation and harmonic distortion. FACTs devices are one of the power electronics revolutions to improve voltage profile, system stability, and reactive power control and to reduce transmission losses. The studied system here is a variable speed wind generation system based on Induction Generator (IG) with integration of different FACTs controllers in the wind farm. To harness the wind power efficiently the most reliable and expensive system in the present era is grid connected doubly fed induction generator. Induction generator with FACTs devices is a suitable economical replacement. The suggested scheme is implemented in MATLAB Simulink with real time parameters of GHARO wind power plant in Sind, and corresponding results and output waveforms proves the potential strength of proposed methodology.